Routine Practice: The Buddhist Fundamental Practice for Self- Development - กวิวํโส, พระมหาอุทิศ (Journal of Educational Review Faculty of Education in MCU, 2018)
The main routine practice principles were laid down the new comers to Buddhism comfortably and easily. The principles were compiled from the Discipline and the Discourse and then classified in groups. The routine practice principles were used by preceptors, revere monks and abbots in training their subordinate-monks and novices in the frame of Dhamma and Vinaya. The concept of routine practice is a form of self-development in Buddhism to train and tame its members in order and to keep Buddhism until now. Keywords: Practice, Personal Development, Buddhism